Manifestations of the gastrointestinal tract in systemic rheumatic diseases: A narrative review - E. V. Moroz; T. V. Popkova; A. E. Moroz (Научно-практическая ревматология, 2022)
Gastrointestinal disorders are important place among the visceral manifestations of systemic autoimmune and immunoinflammatory rheumatic diseases (RD). Pathology of the esophagus, stomach, small and large intestine can vary from moderate functional disorders to the development of severe chronic inflammation with metaplasia and dysplasia of the mucous membrane, the formation of multiple erosions, hemorrhages and deep ulcers. Complications of gastrointestinal pathology in RD, such as bleeding, perforations and strictures, can cause death. This review examines the main clinical manifestations, possibilities of diagnosis and treatment of gastrointestinal lesions in systemic scleroderma, idiopathic inflammatory myopathies, systemic vasculitis, Sjogren’s syndrome and disease, as well as systemic lupus erythematosus.